Oral Rg1 supplementation strengthens antioxidant defense system against exercise-induced oxidative stress in rat skeletal muscles - Yu Szu-Hsien; Huang Hui-Yu; Korivi Mallikarjuna; Hsu Ming-Fen; Huang Chih-Yang; Hou Chien-Wen; Chen Chung-Yu; Kao Chung-Lan; Lee Ru-Ping; Lee Shin-Da; Kuo Chia-Hua (Taylor & Francis Group, 2012)
Abstract Background Previous studies reported divergent results on nutraceutical actions and free radical scavenging capability of ginseng extracts. Variations in ginsenoside profile of ginseng due to different soil and cultivating season may contribute to the inconsistency. To circumvent this drawback, we assessed the effect of major ginsenoside-Rg1 (Rg1) on skeletal muscle antioxidant defense system against exhaustive exercise-induced oxidative stress. Methods Forty weight-matched rats were evenly divided into control (N = 20) and Rg1 (N = 20) groups. Rg1 was orally administered at the dose of 0.1 mg/kg bodyweight per day for 10-week. After this long-term Rg1 administration, ten rats from each group performed an exhaustive swimming, and remaining rats considered as non-exercise control. Tibialis anterior (TA) muscles were surgically collected immediately after exercise along with non-exercise rats. Results Exhaustive exercise significantly (p<0.05) increased the lipid peroxidation of control group, as evidenced by elevated malondialdehyde (MDA) levels. The increased oxidative stress after exercise was also confirmed by decreased reduced glutathione to oxidized glutathione ratio (GSH/GSSG ratio) in control rats. However, these changes were completely eliminated in Rg1 group. Catalase (CAT) and glutathione peroxidase (GPx) activities were significantly (p<0.05) increased by Rg1 in non-exercise rats, while no significant change after exercise. Nevertheless, glutathione reductase (GR) and glutathione S-transferase (GST) activities were significantly increased after exercise in Rg1 group. Conclusions This study provide compelling evidences that Rg1 supplementation can strengthen antioxidant defense system in skeletal muscle and completely attenuate the membrane lipid peroxidation induced by exhaustive exercise. Our findings suggest that Rg1 can use as a nutraceutical supplement to buffer the exhaustive exercise-induced oxidative stress.